Blended language learning: An effective solution but not without its challenges - Christopher Johnson; Debra Marsh (Higher Learning Research Communications, 2014)
The study discussed in this investigation is part of a larger collaborative initiative between Laureate Education and Cambridge University Press (LEP-CUP collaboration). This second phase of the research, completed in 2013, aimed to further explore the conclusions from phase 1 and set out to identify effective and appropriate best practice blended learning models within the network. A study was set up with 36 teachers, all experienced ELT teachers with differing levels of experience in blended language teaching, who took part in extended focus groups discussions sessions prompted by a series of questions. Responses from these groups of teachers indicated that a flipped classroom model is beginning to develop. The authors of this study found evidence of changing approaches to language teaching, changes that are not without their challenges, but for a number of the teachers who participated in this research sample these changes are bringing considerable benefit to their teaching experience. This study offered teachers another opportunity to become change managers for students who need to acquire the autonomous, life-long learning skills of the 21st as they transition into professional life. The scope of this study cannot address and solve all of the issues involved in this process, but it provides a step towards that end.